1988
DOI: 10.1007/bf01965041
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological modification of 12-O-tetradecanoylphorbol-13-acetate induced inflammation and epidermal cell proliferation in mouse skin

Abstract: Topical application of TPA to mouse skin causes oedema (2-6 h) neutrophil influx (3-24 h) and epidermal cell proliferation (24-48 h). Topical application of a cyclooxygenase inhibitor (indomethacin) dual cyclooxygenase and lipoxygenase inhibitors (phenidone and BW755C) a selective lipoxygenase inhibitor (AA861), protein synthesis inhibitors (cycloheximide and actinomycin D) or a glucocorticosteroid (prednisolone) inhibited oedema and neutrophil influx. Systemic administration of an inhibitor of microtubule ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…This experimental model has been suggested for the evaluation of new therapeutic agents for the treatment of inflammatory dermatoses [13].…”
Section: Discussionmentioning
confidence: 99%
“…This experimental model has been suggested for the evaluation of new therapeutic agents for the treatment of inflammatory dermatoses [13].…”
Section: Discussionmentioning
confidence: 99%
“…The inability of ciclosporin to in hibit this response distinguishes it from anti-inflammatory steroids which inhibit all the inflammatory reactions described in this paper [8,11,13], Ciclosporin is therefore a potent inhibitor of cutaneous inflammatory responses which are dependent on protein synthesis and in the mouse it can exert its effect after systemic absorption through the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Myeloperoxidase (MPO) activity, as an index of PMN infiltration, and epidermal proliferation were determined as previously described [8]. Briefly, MPO activity was determined in ear homogenates using Odianisidine hydrochloride and hydrogen peroxide as substrates.…”
Section: Measurement O F Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Edema formation has been estimated as the increase in wet weight of TPA-challenged ears as compared to unchallenged ears. The time course curves done during the development of this model showed that ede ma fonnation reached its maximum at approximately 6.5 h while MPO activity as a parameter of neutrophil influx peaked around 24 h [24]. Therefore, the inflammatory re sponse was measured 6.5 and 24 h after TPA challenge.…”
Section: Effect O F N-3 Pufas On Tpa-induced Inflammationmentioning
confidence: 99%